Challenges of porcine reproductive and respiratory syndrome virus (PRRSV) and the use of the fecal microbiome as an alternative control method - Constance, Laura A. (Kansas State University, 2021)
Porcine reproductive and respiratory syndrome (PRRS) is the most economically devastating swine disease in the United States (U.S.). In the most recent analyses, PRRS was estimated to cost U.S. swine producers approximately $664 million per year with over $360 million alone due to loss in growing pigs. In a population of growing pigs, PRRS results in reduced weight gain, respiratory disease and immunosuppression, increasing infections by primary and secondary pathogens. Significant genetic variation exists among PRRS virus (PRRSV) isolates, which correlates to differences in clinical disease presentation, as well as difficulty in the production of broadly protective vaccines. The objective of the first study was to characterize the clinical outcome of large population of nursery pigs infected with two heterologous PRRSV isolates, NVSL 97-7895 (NVSL; n =189) and KS 2006-72109 (KS06, n=200) and followed for 42 days post-infection. NVSL infection led to delayed, chronic disease resulting in significantly higher morbidity characterized predominately by respiratory disease with a high frequency of altered ambulation, decreased body condition, altered mentation and lower average daily gain (ADG), as well as greater virus replication and increased parenteral antibiotic usage. In contrast, KS06 infection was characterized predominately by fever and acute mortalities early in the infection period. Overall, these results provide evidence that genetically diverse PRRSV isolates manifest differently in both phenotypic presentation and duration. The objective of the second study was to investigate fecal microbiota transplantation (FMT) as a means to prevent porcine circovirus associated disease (PCVAD) in pigs co-infected with PRRSV and PCV-2d. One group of pigs (n = 10) was administered the FMT while a control group (n = 10) was administered a sterile mock-transplant. Over the 42-day post-infection period, the FMT group showed fewer PCVAD-affected pigs, as evidenced by a significant reduction in morbidity and mortality in transplanted pigs, along with increased antibody levels. Overall, this study provides evidence that FMT decreases the severity of clinical signs following co-infection with PRRSV and PCV-2 by reducing the prevalence of PCVAD. The objective of the third was to identify gut microbiome characteristics associated with improved outcome in pigs immunized with a PRRS MLV and co-challenged with PRRSV and PCV2b. Twenty-eight days after vaccination and prior to co-challenge, fecal samples were collected from an experimental population of 50 nursery pigs. At 42 days post-challenge, 20 pigs were retrospectively identified as having high or low growth outcomes during the post-challenge period. Gut microbiomes of the two outcome groups were compared using the Lawrence Livermore Microbial Detection Array (LLMDA) and 16S rDNA sequencing. High growth outcomes were associated with several gut microbiome characteristics. Overall, this study identifies gut microbiomes associated with improved outcomes in PRRS vaccinated pigs following a polymicrobial respiratory challenge and provides evidence towards the gut microbiome playing a role in PRRS vaccine efficacy. The objective of fourth study was to determine the effects of FMT on PRRSV modified live virus (MLV) vaccination. Pigs were split into four groups; two groups of pigs (FMT; n = 20) were administered a fecal microbiota transplant while two control groups (n = 20) were administered a sterile mock-transplant for 7 days prior to vaccination. One FMT and one control group were then vaccinated with the PRRSV MLV vaccine, allowed to mount an immune response (28 days), then were infected with PRRSV and followed for 42 days. During the 28 day vaccination period transplanted pigs had lower, however not significant, viremia levels. Over the 42-day post-infection period, while PRRS MLV vaccination decreased viremia and increased antibody load, there was no effect seen due to transplantation. FMT resulted in overall decreases in microbial diversity; however, shifts in microbial composition were consistent to previous studies. Overall, this study supports the idea that FMT improves PRRSV MLV vaccination by reducing vaccine-associated viremia. The data presented in this dissertation provided evidence PRRSV genetic differences resulting in diverse phenotypic outcomes, and how the gut microbiome can be used to improve or aid in current therapies.
Keywords: Swine; Porcine reproductive and respiratory syndrome virus; Porcine circovirus type 2; Microbiome; Porcine reproductive and respiratory syndrome virus modified live virus vaccine; Fecal microbiota transplant